ANALISIS KEMAMPUAN HIGH ORDER THINKING (HOT) SISWA SMP NEGERI DI KOTA CIMAHI - Yuni Hajar; Ridwan Yanwar; Muhamad Agus Jalaludin; Naskia Achmad; Gita Safira Indriani; Wahyu Hidayat; Euis Eti Rohaeti (IKIP Siliwangi, 2018)
high order thinking skill is an important skill that student must have, especially in mathematics education. In the process of solving problems, students are required to be able to think fundamental and creative. The purpose of this research is to analyze the comparison of high order thinking ability of students in SMPN Cimahi based on school classification. The research method used is experimental with the design of two class and post-test only. the sample taken in this research is the students of class VII SMPN in Cimahi with high classification and moderate classification. The result of this research is there's still a very significant difference in high order thinking the skill of junior high school student in Cimahi city. SMPN with high classification has good high order thinking skills than SMPN with moderate classification. This is due to the following factors, (a) the students have different bits of intelligence; (b) the way students face difficulties (problems) that varies depending on how the students' everyday learning process; (c) the classification of schools have an effect on student’s high order thinking skill.